Empowerment and training in making herbal tea to utilize herbal plants and prevent degenerative diseases - Herman Herman; Andi Tenri Kawareng; Arman Rusman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Teluk Pemedas is one of the sub-districts in the Samboja sub-district, Kutai Kartanegara, East Kalimantan Province. Previous health examination data showed that the presentation of hypertension in the Teluk Pamedas community was 28% and hypercholesterolemia was 20%. The use of herbal plants as an alternative treatment has been widely used. Plants that have antihypertensive and antihypercholesterolemic activity are rosella flowers, pandan leaves, and cinnamon. Research results show that this plant can lower blood pressure for hypertension sufferers. The aim of carrying out this activity is to increase public knowledge about degenerative diseases and the use of local herbal plants to add economic value. This activity was carried out in two stages, with an education method regarding degenerative diseases, then continued with a training method for making herbal tea preparations from a combination of rosella flowers (Hibiscus sabdariffa), pandan leaves (Pandanus amaryllifolius) and cinnamon (Cinnamomum burmanii). The partner of this activity is Dasawisma Teluk Pamedas sub-district, Samboja, Kutai Kartanegara East Kalimantan. This activity provides benefits to the community regarding efforts to prevent degenerative diseases and implement a healthy lifestyle and improve skills in processing herbal plants.